A protein interaction mechanism for suppressing the mechanosensitive Piezo channels. Issue 1 (December 2017) - Zhang, Tingxin; Chi, Shaopeng; Jiang, Fan; Zhao, Qiancheng; Xiao, Bailong
Abstract Piezo proteins are bona fide mammalian mechanotransduction channels for various cell types including endothelial cells. The mouse Piezo1 of 2547 residues forms a three-bladed, propeller-like homo-trimer comprising a central pore-module and three propeller-structures that might serve as mechanotransduction-modules. However, the mechanogating and regulation of Piezo channels remain unclear. Here we identify the sarcoplasmic /endoplasmic-reticulum Ca2+ ATPase (SERCA), including the widely expressed SERCA2, as Piezo interacting proteins. SERCA2 strategically suppresses Piezo1 via acting on a 14-residue-constituted intracellular linker connecting the pore-module and mechanotransduction-module. Mutating the linker impairs mechanogating and SERCA2-mediated modulation of Piezo1. Furthermore, the synthetic linker-peptide disrupts the modulatory effects of SERCA2, demonstrating the key role of the linker in mechanogating and regulation. Importantly, the SERCA2-mediated regulation affects Piezo1-dependent migration of endothelial cells. Collectively, we identify SERCA-mediated regulation of Piezos and the functional significance of the linker, providing important insights into the mechanogating and regulation mechanisms of Piezo channels. Mechanosensitive Piezo channels are important for a wide range of mechanotransduction processes. Here the authors show that Piezos interact with sarcoplasmic /endoplasmic-reticulum Ca2+ ATPases (SERCA) and give mechanistic insights into mechanogating and SERCA2-mediated regulation of Piezo1.